PENGARUH PENDIDIKAN dan PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS XYZ PROVINSI RIAU - Iskandar, Iskandar; Risman, Risman (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This research was conducted at the Department of Cooperatives and Small and Medium Enterprises Riau Province, located in the Sudirman Complex Lt.4 Pekanbaru Riau Governor's Office. The purpose of this study to analyze the influence of education and training on the performance of employees at the Department of Cooperatives and Small and Medium Enterprises Riau Province, to analyze the effect of motivation on employee performance in the Department of Cooperatives and Small and Medium Enterprises Riau province and to analyze the influence of education and training and motivation on employee performance the Department of Cooperatives and Small and Medium Enterprise Riau Province. To achieve these objectives the research carried out by using a sample of 100 people, using Census. Methods of data analysis using simultaneous test and partial test (multiple linear regression analysis with SPSS Windows version 17). Recommendations can be the author to ask is should service Cooperatives and Small and Medium Enterprises Riau Province regard education as well as training followed by employees and the department should conduct an evaluation of the restrictions that participants will attend training, because employees menaganggap with the restrictions of participants who wish to attend training tantamount to banning employees to increase knowledge to broaden that can support the employee's performance